2019
DOI: 10.1519/jsc.0000000000002422
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Back Squats on Countermovement Jump Performance Across Multiple Sets of a Contrast Training Protocol in Resistance-Trained Men

Abstract: The present study was designed to evaluate the voluntary post-activation potentiation (PAP) effects of moderate (MI) or high intensity (HI) back squat exercises on countermovement jump (CMJ) performance across multiple sets of a contrast training protocol. Sixty resistance-trained male subjects (age, 23.3 ± 3.3 y; body mass, 86.0 ± 13.9 kg; parallel back squat 1-repetition maximum [1-RM], 155.2 ± 30.0 kg) participated in a randomized, cross-over study. After familiarization, the subjects visited the laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 25 publications
8
61
1
Order By: Relevance
“…Previous studies reported lower limb strength improvement following traditional resistance exercises (e.g. squat) (1). Several explanatory factors may be considered such as physiological and biochemical factors (3,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported lower limb strength improvement following traditional resistance exercises (e.g. squat) (1). Several explanatory factors may be considered such as physiological and biochemical factors (3,31).…”
Section: Discussionmentioning
confidence: 99%
“…Such phenomena may explain the improvements in lower limb performance reported in the current study (6). Previous evidence supports the positive effect of traditional resistance methods in stimulating acute muscle responses (1,16). Research on PAP response following an EOL exercise using a flywheel ergometer is missing (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-activation potentiation (PAP) is a physiological phenomenon associated with an acute improvement in muscular performance after a resistance training protocol [1,2]. Neuromuscular, mechanical and biochemical changes may induce these temporary improvements in performance but the exact underlying mechanisms are still not fully understood [1,3]. The most strongly supported explanation for the effects of PAP relates to a greater rate of cross-bridge attachment as a result of phosphorylation of myosin regulatory light chains during muscle contraction [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most strongly supported explanation for the effects of PAP relates to a greater rate of cross-bridge attachment as a result of phosphorylation of myosin regulatory light chains during muscle contraction [4]. Furthermore, PAP is proposed to result from increased sensitivity of contractile proteins to calcium (Ca 2+ ) released from the sarcoplasmic reticulum, resulting in a cascade of events leading to an enhanced muscular response [35].…”
Section: Introductionmentioning
confidence: 99%